Ru, Pd doped WO3 nanomaterials: a synergistic effect of noble metals to enhance the acetone response properties - Kodam, Pavan M.; Ghadage, Pandurang A.; Nadargi, Digambar Y.; Shinde, K. P.; Mulla, Imtiaz S.; Park, J. S.; Suryavanshi, Sharad S. (Ceramics International, 2022)
Noble metals (NMs) have an enormous impact on the intrinsic properties of the metal oxides. We report the synergistic effect of Ruthenium (Ru) and Palladium (Pd) noble metals on the enhancement of gas sensing properties of pure tungsten oxide (WO3). The gas sensing material is synthesized by simple and straight forward precipitation route, and its physico-chemical analyses are determined using XRD, FESEM, TEM/HRTEM, FFT, UV-Vis, XPS, EDAX, and BET measurements. Use of the developed material as a gas sensor is evaluated using several target gases (oxidizing as well as reducing), with acetone showing the best selectivity. The noble metal doping and hence catalytic action improved the gas response qualities. The synergistic effect of Ru and Pd on WO3 gas response properties are identified, where the effect is 99.80% sensitivity, and lower response/recovery time (10 s and 2 min) at 300 degrees C operating temperature. Nonetheless, the sensors displayed better gas sensing properties even at lower operating temperatures ranging from 200 to 275 degrees C. In addition, the synergistic effect has displayed the dramatic enhancement in the sensitivity to 76.44% at barely 10 ppm acetone concentration. This particular result will undoubtedly be helpful for diagnostic purpose of diabetic patients, and a strong candidate for prospective gas sensing applications, particularly acetone.
Keywords: Acetone vapours; Precipitation route; Ru -Pd doping; synergistic effect; WO3

Sponge microflowers of NiCo2O4: a versatile material for high performance supercapacitor - Ghadage, Ambar; Kodam, Pavan; Nadargi, Digambar; Shinde, K. P.; Mulla, Imtiaz; Park, J. S.; Suryavanshi, Sharad (Journal of Porous Materials, 2022)
We report the development of well optimised NiCo2O4 microflowers for high performance supercapacitor application. The efforts were made to optimise the electrode material by tuning the synthetic as well as electrolyte concentration parameters such as (i) hydrothermal reaction temperature, (ii) hydrothermal reaction time, (iii) sintering temperature, and (iv) electrolyte concentration. The physico-chemical and supercapacitive properties were analysed using TGA, XRD, SEM/TEM/HRTEM, XPS, BET, and electrochemical measurements. The well optimised electrode material was obtained at 150 degrees C hydrothermal reaction temperature, 12 h of hydrothermal reaction time, 300 degrees C sintering temperature, and 3 M KOH electrolyte concentration. The optimised sample displayed high specific -capacitance (1478 F/g), -energy density (16.5 Wh/kg), and -power density (248 W/kg). The specific capacitance can be retained to 97.61% after 1000 cycles. The developed NiCo2O4 microflower structures are well optimised and offer great promise for future industrial applications.
Keywords: hydrothermal; Microflowers; Nickel cobaltite; supercapacitor

Bismuth ferrite based acetone gas sensor: evaluation of graphene oxide loading - Ghadage, Pandurang; Shinde, K. P.; Nadargi, Digambar; Nadargi, Jyoti; Shaikh, Hamid; Alam, Mohammad Asif; Mulla, Imtiaz; Tamboli, Mohaseen S.; Park, J. S.; Suryavanshi, Sharad (RSC Advances, 2024)
We report a BiFeO3/graphene oxide (BFO/GO) perovskite, synthesized using a CTAB-functionalized glycine combustion route, as a potential material for acetone gas sensing applications. The physicochemical properties of the developed perovskite were analysed using XRD, FE-SEM, TEM, HRTEM, EDAX and XPS. The gas sensing performance was analysed for various test gases, including ethanol, acetone, propanol, ammonia, nitric acid, hydrogen sulphide and trimethylamine at a concentration of 500 ppm. Among the test gases, the developed BFO showed the best selectivity towards acetone, with a response of 61% at an operating temperature of 250 degrees C. All the GO-loaded BFO samples showed an improved gas sensing performance compared with pristine BFO in terms of sensitivity, the response/recovery times, the transient response curves and the stability. The 1 wt% GO-loaded BiFeO3 sensor showed the highest sensitivity of 89% towards acetone (500 ppm) at an operating temperature of 250 degrees C. These results show that the developed perovskites have significant potential for use in acetone gas sensing applications. CTAB-functionalized glycine combustion yields BiFeO3/graphene oxide (BFO/GO) perovskite for acetone gas detection.